A Comparison of Three Methods to Increase Scleral Contact Lens On-Eye Stability. Issue 6 (November 2015) - Ticak, Anita; Marsack, Jason D.; Koenig, Darren E.; Ravikumar, Ayeswarya; Shi, Yue; Nguyen, Lan Chi; Applegate, Raymond A.
Abstract : Purpose: To quantify on-eye rotational and translational stability of three scleral contact lens stabilization methods and to model the variation in visual acuity when these movements occur in a wavefront-guided correction for highly aberrated eyes. Methods: Three lens stabilization methods were integrated into the posterior periphery of a scleral contact lens designed at the Visual Optics Institute. For comparison, a lens with no stabilization method (rotationally symmetric posterior periphery) was designed. The lenses were manufactured and lens movements were quantified on 8 eyes as the average SD of the observed translations and rotations over 60 min of wear. In addition, the predicted changes in acuity for five eyes with keratoconus wearing a simulated wavefront-guided correction (full correction through the fifth order) were modeled using the measured movements. Results: For each lens design, no significant differences in the translation and rotation were found between left and right eyes, and lenses behaved similarly on all subjects. All three designs with peripheral stability modifications exhibited no statistically significant differences in translation and rotation distributions of lens movement and were statistically more stable than the spherical lens in rotation. When the measured movements were used to simulate variation in visual performance, the 3 lenses with integrated stability methods showed a predicted average loss in acuity from the perfectly aligned condition of approximately 0.06 logMAR (3 letters), compared with the loss of over 0.14 logMAR (7 letters) for the lens with the spherical periphery. Conclusion: All three stabilization methods provided superior stability, as compared with the spherical lens design. Simulations of the optical and visual performance suggest that all three stabilization designs can provide desirable results when used in the delivery of a wavefront-guided correction for a highly aberrated eye.